Analysis of Bacterial Diversity in Different Types of Daqu and Fermented Grains From Danquan Distillery - Shang, Changhua; Li, Yujia; Zhang, Jin; Gan, Shanling (Frontiers in Microbiology, 2022)
Abstract Bacterial communities in high-temperature Daqu and fermented grains are important for brewing Jiang-flavor Baijiu such as Danquan Baijiu. Daqu is a saccharifying and fermenting agent, which has a significant impact on the flavour of Baijiu. However, bacterial communities in three different types of samples from Danquan distillery (dqjq_ck, dqjqcp and dqjp3) were still unclear, which limited further development of Danquan Baijiu. The “dqjq_ck” and “dqjqcp” indicate high-temperature Daqu at day 45 and day 135, respectively. The “dqjp3” indicates fermented grains. In this paper, the bacterial communities of three samples were analyzed by Illumina Miseq high-throughput sequencing. The bacterial communities of three samples were primarily composed of thermophilic bacteria and bacteria with stress resistance. The most abundant species in dqjq_ck, dqjqcp and dqjp3 were Comamonas, Bacillus and unclassified Lactobacillales, respectively. The main bacteria included Bacillus, Comamonas, Myroides, Paenibacillus, Acetobacter, Kroppenstedtia, Staphylococcus, Saccharopolyspora, Planifilum, Lactobacillus, Acinetobacter, Oceanobacillus, Enterococcus, Thermoactinomyces, Lactococcus, Streptomyces, Saccharomonospora, Tepidimicrobium, Anaerosalibacter, unclassified_Lactobacillales, unclassified_Thermoactinomycetaceae_1, unclassified_Bacillaceae_2, unclassified_Bacillales, unclassified_Microbacteriaceae, unclassified_Rhodobacteraceae, unclassified_Actinopolysporineae, and unclassified_Flavobacteriaceae in three samples (percentage was more than 1% in one of three samples). Through our study, the succession of microbiota in three samples representing three important stages of Danquan Baijiu brewing were revealed. This paper laid a good foundation for understand the fermentation mechanism and screening some excellent indigenous bacteria to improve the quality of Danquan Baijiu in near future.